Indignation and Politics: reflections from Hannah Arendt’s thinking. (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
Starting from highlighting some specific moments in Arendt‟s works critically dealing with sentimentality matters, we will focus on a specific aspect: the place of indignation when narrating, telling, and constructing the history of a community and, at the same time, opening a public space. This is characterized by Arendt as an elementary space, where others appear to me and I appear before them. (Arendt, Human Condition 221), originating the political aspect. This view allows us to rebuild the possible relationship between indignation and politics in this German author‟s views.
Keywords: Indignation; Feelings; Politics; History; Public Space